The Influence of Health Education on Knowledge of Hypertension in Hypertension Patients at Belimbing Health Center in Padang City - Eliza, Eliza; Herlina, Andika; Yanti, Etri; Lesmana, Sonya (STIKES Syedza Saintika Padang, 2025)
ABSTRACT Hypertension may be a degenerative infection that's the third cause of passing around the world, and the repeat rate is expanding each year.One of the components causing tall blood pressure could be a need of information.One way to extend information around hypertension is through wellbeing instruction.The point of this ponder was to degree the effectiveness of hypertension wellbeing instruction for hypertensive patients at the Belimbing Community Wellbeing Center, Padang City.This sort of investigate may be a single gather pretest and posttest some time recently the test.The ponder populace included all 126 individuals enduring from tall blood pressure at the Belimbing Community Wellbeing Center.The examining strategy was a focused on test with a test measure of 30 individuals.Information will be collected employing a survey.univariate and bivariate.The normal level of information approximately hypertension some time recently being given wellbeing instruction was 4.73, and the normal level of information approximately hypertension after being given wellbeing instruction was 8.00.There's an impact of wellbeing instruction on information of hypertension in hypertensive patients at the Belimbing Community Wellbeing Center, Padang City in 2024 (p-value = 0.000).The conclusion of this investigate is that wellbeing instruction impacts information around hypertension in hypertensive patients.Puskesmas supervisors are empowered to get ready wellbeing instruction programs almost hypertension for hypertensive patients twice a month at Berimbing Puskesmas. Keywords: Health Education, , Hypertension, Knowledge